1997
DOI: 10.1111/j.1365-2702.1997.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses achieve quality with pre‐assessment clinics

Abstract: Nurses in a group of Wolverhampton Hospitals carried out a local research study to identify not only the level of patient satisfaction with pre-assessment clinics (PAC), but also what care nurses delivered in these clinics. Data were collected using both ethnographic and survey methods. Patients found the PAC visit valuable: it reduced stress and provided much needed information about the coming surgery. The skills nurses used and the tasks carried out were consistent throughout the Trust, and reflected the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, the number of patients included in the study is not clear. Clinch (1997) used both survey and ethnographic approaches to evaluate four pre‐admission clinics in different medical specialities. Bond & Barton (1994) conducted a patient satisfaction survey and distributed questionnaires to 92 patients.…”
Section: Background To the Studymentioning
confidence: 99%
“…However, the number of patients included in the study is not clear. Clinch (1997) used both survey and ethnographic approaches to evaluate four pre‐admission clinics in different medical specialities. Bond & Barton (1994) conducted a patient satisfaction survey and distributed questionnaires to 92 patients.…”
Section: Background To the Studymentioning
confidence: 99%
“…This is unfortunate, as preoperative instruction has beneficial affects with regard to patient knowledge (Lepczyk et al . 1990, Clinch 1997, Clements & Melby 1998), anxiety (Leigh et al . 1977), postoperative pain, length of hospitalization (Klafta & Roizen 1996, Shuldham 1999), and psychological coping outcomes (Gammon & Mulholland 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive information may have an opposite effect in the form of increased anxiety, however, if the information given is not adapted to the individual and balanced in the proper manner 35 . Studies have shown that patients who are prepared in special departments with appropriate information experience less anxiety than other patients 36–38 . These patients experience a feeling of being well taken care of and believe that the medical examinations are necessary and that the preparations for surgery are well‐organized, which contributes to their feelings of security and well‐being 39 …”
Section: Literature Reviewmentioning
confidence: 99%